APPLIED MISSIOLOGY OF EDUCATION FOR SUNDAY SCHOOL CHILDREN (Lembaga Pengembangan Kinerja Dosen, 2022)
Ideally, missiology education is applied to teachers and preachers who are positioned for adults who already have qualified literacy and religious abilities. In the application of youth and children's education, it is recommended to parents and teachers so that parents of these students or children can learn the rules of learning. Missiology is learning when someone gives testimony and a story about superpowers or outside forces reason (about the power of God, Prophets, and religious leaders), so that they provide a personal experience and story that can convince people, whether in any religion. Missiology learning is not part of the context of education in schools, but the context of missiology should have been taught by parents and teachers when the children studied religion. This study aims to reveal how simple missiology learning can be applied so that children in their development to adulthood have the ability and uphold the mind in upholding supernatural values.